Voyage rights in review: Indonesian tourism and aviation legislation - Adhy Riadhy Arafah; Yaries Mahardika Putro; Alifia Nuril Bais; Son Solita; Satria Unggul Wicaksana Prakasa (Cogent Social Sciences, 2024)
Indonesia’s ratification of the Montreal Convention 1999 in 2016 and its implementation in national law has significantly affected the protection rights of Indonesian citizens globally and locally. This Convention ensures that Indonesian travelers are entitled to international benefits, provisions, and compensation for damages caused by airline services. Through an examination of Indonesian statutes, cases, and a comparative approach, the authors have concluded that there is a significant need to amend the Indonesian Aviation Act to solve the conflict of law that exists between the Montreal Convention of 1999 and Indonesian law. Specifically, this conflict exists with respect to the implementation of the Montreal Convention 1999 in Indonesian domestic law because of the superior hierarchy of the Convention over Indonesian law. While the Montreal Convention 1999 applies to all international carriage activities, the Indonesian Aviation Act covers domestic and international carriages only to and from Indonesia’s territory and to all Indonesian carriers outside Indonesia’s territory. This study discusses the legal consequences that impact Indonesian air travelers according to the differences between international conventions and domestic law.